Rancang Bangun Inertial Measurement Unit Sebagai Sistem Monitoring Kendaraan Bergerak Berbasis Sensor Accelerometer dan Gyroscope - Achmad Hidayatno; Wahyudi Wahyudi (Universitas Syiah Kuala, 2011)
IMU (Inertial Measurement Unit) is very important in navigation and control systems. The MU that has six degrees of freedom consists of three accelerometer sensors and three gyroscope sensors, each placed on three axes (x, y, and z) and orthogonal to each other. Vehicle monitoring systems that exist at present only provide information on the vehicle at two degrees of freedom (X and Y), so that the rotation of the vehicle is unknown. To be able to find the vehicle as a whole, namely the six degrees of freedom consisting of three position data and three rotation data, it would require an IMU with six degrees of freedom, namely by using the accelerometer and gyroscope sensor mounted on all three axes. In the research has been conducted design IMU sensors as the vehicle monitoring system with six degrees of freedom, so that can know the condition of the vehicle in six degrees of freedom, namely the position x, y, and z and rotation in three axes (roll, pitch, and yaw). IMU system uses an antenna transceiver for data transmission medium. We did the tests of IMU sensors in the initial output, motion response, and testing of navigation. Tests performed on laboratory scale to perform the calibration of the IMU sensor and then performed field tests using a motor vehicle. In laboratory-scale testing is not required transmitter and receiver antennas. Based on the results of the research shown the measurements of the attitude angle 90o with the axis of the rotary axis x, axis y, z axis with 7 variations of the test result in an average MSE of 2.277o x-axis, y axis of 2.519o, z-axis of 3.334o respectively and the measurement to the distance of 30 cm for 7 variations f testing resulted in an average MSE of 2.659 cm for the x-axis, 3.995 cm for the y-axis, and 2.142 cm for the z axis.